Effect of Peripheral Heart Action on Body Composition and Blood Pressure in Women with High Blood Pressure - Nabilpour, Maghsoud; Mayhew, Jerry (International Journal of Sport Studies for Health, 2018)
Objectives: Exercise is non-medical treatment and low-risk strategy for people with hypertension. Therefore, the aim of this study was to evaluate the effect of peripheral heart action (PHA) on body composition and blood pressure in women with high blood pressure.Methods: Twenty women (age = 38 - 46 years, BMI = 21 - 31 kg/m2) who had high blood pressure (135/88 mm Hg) volunteered to participate. Ten were randomly selected and submitted to 32 PHA exercise sessions. The remaining 10 participants served as a non-exercise control group. Systolic (SBP) and diastolic blood pressure (DBP), skinfold, and 1RM tests of maximum strength were determined before and after 36 exercise sessions.Results: SBP and DBP were decreased significantly (P < 0.05) in the PHA group but not in the non-exercise control group. Furthermore, the training group made significant improvements in test of one-repetition maximum and body composition compared to the control group (P < 0.05).Conclusions: Resistance exercises using the PHA approach can be considered as a low-risk treatment for people with high blood pressure in order to improve blood pressure, increase muscular strength, and enhance overall fitness.